2015
DOI: 10.1016/j.jad.2015.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Maternal response to child affect: Role of maternal depression and relationship quality

Abstract: Background Maternal depression is associated with negative outcomes for offspring, including increased incidence of child psychopathology. Quality of mother-child relationships can be compromised among affectively ill dyads, such as those characterized by maternal depression and child psychopathology, and negatively impact outcomes bidirectionally. Little is known about the neural mechanisms that may modulate depressed mothers’ responses to their psychiatrically ill children during middle childhood and adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…However, in one study during this developmental period, Morgan et al. () found that mothers with a greater history of recurrent depressive episodes recruited higher levels of self‐related processing regions—including the precuneus and precentral gyrus—and ventromedial prefrontal cortex (vmPFC) when viewing video clips of their adolescent expressing negative emotion (Morgan et al., ). Moreover, authors found that lower maternal warmth and higher maternal hostility were associated with less activation in regulatory (e.g., vmPFC, dlPFC) and self‐related processing regions (e.g., precuneus, PCC) to the video clips of their adolescent.…”
Section: Caregiver Affective Neurobiological Processing Of Negative Smentioning
confidence: 99%
See 2 more Smart Citations
“…However, in one study during this developmental period, Morgan et al. () found that mothers with a greater history of recurrent depressive episodes recruited higher levels of self‐related processing regions—including the precuneus and precentral gyrus—and ventromedial prefrontal cortex (vmPFC) when viewing video clips of their adolescent expressing negative emotion (Morgan et al., ). Moreover, authors found that lower maternal warmth and higher maternal hostility were associated with less activation in regulatory (e.g., vmPFC, dlPFC) and self‐related processing regions (e.g., precuneus, PCC) to the video clips of their adolescent.…”
Section: Caregiver Affective Neurobiological Processing Of Negative Smentioning
confidence: 99%
“…However, based on findings from Morgan et al. (), the direction of effects related to self‐related or referential processing regions remains unclear—it may be that higher precuneus/PCC activation is associated with poorer maternal functioning (e.g., depression) or that lower precuneus/PCC is associated with maladaptive parenting (e.g., maternal hostility).…”
Section: Caregiver Affective Neurobiological Processing Of Negative Smentioning
confidence: 99%
See 1 more Smart Citation
“…22 Additionally, stronger anterior insula activation in response to negative infant stimuli has been reported in intrusive and depressed mothers. 23,24 Hence, increased salience of infants' negative cues and heightened affective response to them may promote emotionally overwhelmed, intrusive responses in mothers, instead of sensitive exchange and bonding with the child. Furthermore, sensitive mothers show stronger activations in the lateral frontal pole region and inferior frontal gyrus as a result of negative cues from their own infant, 23,25 and nondepressed mothers (but not depressed mothers) showed greater response to their infant's cry in the dorsal anterior cingulate cortex.…”
Section: J Psychiatry Neurosci 2018;43(4)mentioning
confidence: 99%
“…Since lifetime history of a mental disorder influenced maternal sensitivity, we controlled for this in the fMRI analyses, underlining the specificity of the observed neural changes for ELM. Contrary to previous studies, [19][20][21][22][23][24][25][26] we focused on mothers of primary-school-aged children, an age group that, to our knowledge, has not been addressed before.…”
mentioning
confidence: 99%